Beyond Aid : How Much Should African Countries Pay to Borrow? - Gueye, Cheikh (IMF Working Papers; Working Paper ;, 2010)
Post debt relief, the number of African countries considering accessing international capital markets, often to fund large infrastructure projects, is increasing. Potential risks of capital inflows are well known but the literature offers little help to estimate the cost of borrowing internationally for the first time. This paper proposes a two-step approach to estimate the sovereign credit rating and interest rate cost of a country considering borrowing externally. Estimates can be used to assess the costs and benefits of different financing options. The method can also be used to construct foreign currency as well as domestic local currency yield curves.